Clinical Characterization and Survival of Patients with Borderline Elevation in Pulmonary Artery Pressure. (1st December 2013) - Heresi, Gustavo A.; Minai, Omar A.; Tonelli, Adriano R.; Hammel, Jeffrey P.; Farha, Samar; Parambil, Joseph G.; Dweik, Raed A.
Abstract : Normal resting mean pulmonary artery pressure (PAP) is 8–20 mmHg. Pulmonary hypertension is defined as mean PAP of ≥25 mmHg. Borderline PAP levels of 21–24 mmHg are of unclear significance. We sought to determine the clinical characteristics and survival of subjects with mean PAP of 21–24 mmHg. We examined 1, 491 patients enrolled in the Cleveland Clinic Pulmonary Hypertension Registry between February 1990 and May 2012 with baseline right heart catheterization. The relationship between PAP and all‐cause mortality was assessed by Cox models and a tree‐based analysis. Sixty‐three patients had borderline PAP (underlying conditions: 12 left heart disease, 20 respiratory disease, 17 connective‐tissue disease, 4 others, and 10 none). We then compared 3 groups: borderline PAP without heart or lung disease ( n = 31), normal PAP without heart or lung disease ( n = 51), and category 1 pulmonary arterial hypertension (PAH; n = 387). Borderline‐PAP patients had levels of hemodynamic and functional compromise between those for normal‐PAP patients and those for patients with PAH. Borderline PAP was associated with increased mortality compared to normal PAP (hazard ratio: 4.03 [95% confidence interval: 0.78–20.80], P = 0.099). A tree‐based analysis demonstrated almost identical cut points in mean PAP (≤20, 21–26, and ≥27 mmHg) associated with differential survival ( P < 0.001). Connective‐tissue disease and an elevated transpulmonary gradient were predictors of worse survival in the borderline‐PAP population. Borderline PAP elevation is associated with decreased survival, particularly in the context of connective‐tissue disease and an elevated transpulmonary gradient.